Impacts of Mootral on Methane Production, Rumen Fermentation, and Microbial Community in an in vitro Study - Ahmed, Eslam; Yano, Rintaro; Fujimori, Miho; Kand, Deepashree; Hanada, Masaaki; Nishida, Takehiro; Fukuma, Naoki (Frontiers in Veterinary Science, 2021)
Methane mitigation strategies have a two-sided benefit for both environment and efficient livestock production. This preliminary short-term in vitro trial using Mootral (garlic and citrus extracts), a novel natural feed supplement, was conducted to evaluate its efficacy on rumen fermentation characteristics, methane production, and the bacterial and archaeal community. The experiment was performed as a batch culture using rumen fluid collected from sheep, and Mootral was supplemented in three concentrations: 0% (Control), 10%, and 20% of the substrate (50% Grass:50% Concentrate). The rumen fermentation data and alpha diversity of microbial community were analyzed by ordinary one-way analysis of variance. The relative abundance and statistical significance of families and operational taxonomic units (OTUs) among the groups were compared by Kruskal–Wallis H test using Calypso software. After 24-h incubation at 39°C, Mootral in a dose-dependent manner improved the production of total volatile fatty acids and propionate while it reduced the acetate proportion and acetate/propionate ratio. The total produced gas was two times higher in the Mootral-supplemented groups than control (P < 0.01), while the proportion of methane in the produced gas was reduced by 22% (P < 0.05) and 54% (P < 0.01) for 10 and 20% Mootral, respectively. Mootral did not change pH, digestibility, and ammonia-nitrogen. Microbial community analyses showed that Mootral effectively changed the ruminal microbiome. The bacterial community showed an increase of the relative abundance of the propionate-producing family such as Prevotellaceae (P = 0.014) and Veillonellaceae (P = 0.030), while there was a decrease in the relative abundance of some hydrogen-producing bacteria by Mootral supplementation. In the archaeal community, Methanobacteriaceae was decreased by Mootral supplementation compared with control (P = 0.032), while the Methanomassiliicoccaceae family increased in a dose-dependent effect (P = 0.038). The results of the study showed the efficacy of the new mixture to alter the ruminal microbial community, produce more propionate, and reduce microbial groups associated with methane production, thus suggesting that Mootral is a promising natural mixture for methane reduction from ruminants.